2006
DOI: 10.1292/jvms.68.865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olprinone on Myocardial Ischemia-Reperfusion Injury in Dogs

Abstract: ABSTRACT. We investigated the effect of olprinone on canine myocardial pump function and myocardial damage after ischemia-reperfusion injury. Three dogs of the experimental group were given olprinone (Olprinone group) and another 3 dogs were served as control (Intact group). All animals were occluded left anterior descending artery for 60 min, followed by 6 hr of reperfusion. In the experiment, hemodynamics, infarct area, creatine kinase and troponin-I were measured. Olprinone infusion induced significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Milrinone or olprinone, when administered before ischemia-reperfusion, was cardioprotective and reduced infarct size in dogs (Setoyama et al, 2006). Amrinone and milrinone decrease infarct size in rabbit hearts with coronary artery branch occlusion via vasodilation to increase myocardial perfusion in the tissue surrounding the ischemic zone (Rump et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Milrinone or olprinone, when administered before ischemia-reperfusion, was cardioprotective and reduced infarct size in dogs (Setoyama et al, 2006). Amrinone and milrinone decrease infarct size in rabbit hearts with coronary artery branch occlusion via vasodilation to increase myocardial perfusion in the tissue surrounding the ischemic zone (Rump et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in laboratory animals 15 and dogs 16 have reported on the diagnostic use of cTnI and concluded that cTnI is both sensitive and specific for the diagnosis of acute myocardial injury. The results of this study confirm such findings.…”
Section: Discussionmentioning
confidence: 99%
“…Flunixin-meglumine f (1.1 mg/kg, IV) was given for pyrexia and alleviation of gastrointestinal pain as needed. Blood was collected from the indwelling jugular catheter at 4,6,8,12,16,20,24,36,48,72, and 80 hours (Group A) and at 12, 24, 36, 48, 72, 96, 120, and 144 hours (Group B) after monensin administration for serum biochemical analyses and cTnI measurement. The blood was divided equally and put into tubes without anticoagulant.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of PDE‐III inhibitors has been demonstrated in isolated heart preparations 5,17,18 . However, only two in vivo studies have demonstrated pre‐conditioning effects in dogs 19,20 . These findings might be related to increased collateral flow.…”
Section: Discussionmentioning
confidence: 99%